Analyzing the Performance of an Institutional Scientific Repository – A Case Study - Rodrigues, M.E.P. (2012)
Scientific knowledge evolution is mainly based on an effective dissemination of research results. The concept of Open Access gives us the theoretical foundation of a model for accessing scientific knowledge, free from the constraints of traditional publishing and technologically supported by the Internet. Institutional Repositories are information systems that allow preserving, storing and disseminating scientific knowledge produced in higher education and scientific research institutions. They increase the visibility and the citation level of the documents. They also contribute to minimizing negative aspects like plagiarism of content because documents are exposed to peers in real time. As an alternative way to the traditional system of publishing scientific research content, repositories are developed in a cultural climate of great visibility leading to an immediate critical evaluation by peers. The Scientific Repository of the Polytechnic Institute of Castelo Branco – Portugal (RCIPCB) was created in 2009 but its official presentation took place in January 2010. Its main purposes are promoting Open Access (OA), and preserving and disseminating the scientific knowledge produced at the Polytechnic Institute of Castelo Branco (IPCB). Using DSpace as a technological platform, RCIPCB is an institutional project supported by the president of the IPCB. Therefore, the present study was developed with the aim of analyzing the performance of RCIPCB considering the evolution and growth in terms of users, archiving and self-archiving, the number of published documents (scientific) versus deposited documents in 2010 and the heterogeneity among communities/collections and its causes. Data were collected in RCIPCB, in the 2010 scientific publication list of the institute and through a questionnaire survey distributed among the members of the community with most documents deposited and those of the community with the fewest documents. For data collected in RCIPCB and in the publication list, average, standard deviation and counts were calculated. Data collected from questionnaires were analyzed with SPSS. The results show that RCIPCB indicates an asymmetric growing dynamics. Nevertheless, it reflects the institutional organization, in the sense that the communities related to the older schools possess more documents than the communities related to more recent schools. Communities having higher numbers of deposited documents seem to have also higher levels of searches and downloads. Therefore, it increases significantly the visibility of the institution and its researchers. Concerning the 2010 scientific production when compared with the deposit level of the corresponding community, the results show that the number of documents deposited is much lower than the number of published documents. Data obtained from the questionnaire answers from the communities The School of Agriculture (ESACB) and The School of Applied Arts (ESART) suggest that the strategy of communication used by RCIPCB is correct because everybody knows about the Repository. However, that is not related to the number of documents deposited. They also suggest that the strategy is not efficient and it needs some improvements in order to become effective. Considering the results it is clear that RCIPCB needs to have a mandatory depositing policy that might also be extended to user registration. Those factors would minimize both the heterogeneity and the asymmetric growth of communities and collections. Moreover, it would also decrease the difference between scientific production and the corresponding deposit in RCIPCB.